Higher Education: Pandemic COVID-19 - Valdivia Vizarreta, Paloma (2020)
The health emergency situation led the universities that provide face-to-face training to adapt to the virtuality. During this period their actions have been crucial to safeguard educational progress (Wang et al., 2020), within their possibilities, they have made efforts to do so in an agile and fast way, not planned. They have used the technological resources at their disposal, they have coordinated an intense work of reprogramming, learning and adaptation by teachers and students (Crawford, 2020). All this, along with the reconciliation between these new learning scenarios at home and their family life.